2023
DOI: 10.3390/metabo13080884
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthetic Pathways of Hormones in Plants

Abstract: Phytohormones exhibit a wide range of chemical structures, though they primarily originate from three key metabolic precursors: amino acids, isoprenoids, and lipids. Specific amino acids, such as tryptophan, methionine, phenylalanine, and arginine, contribute to the production of various phytohormones, including auxins, melatonin, ethylene, salicylic acid, and polyamines. Isoprenoids are the foundation of five phytohormone categories: cytokinins, brassinosteroids, gibberellins, abscisic acid, and strigolactone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 216 publications
(324 reference statements)
0
8
0
Order By: Relevance
“…BRs have a wide range of physiological functions, such as plant height, plant type, flowering time, plant root growth, stem elongation, leaf extension, microtubule system development, plant morphology in dark conditions, pollen tube elongation, and seed development [33][34][35]. The main signal transduction pathways of BRs have been established, and the key gene functions of these pathways have been verified in A. thaliana; the DET2 gene is a key rate-limiting gene in brassinolide biosynthesis pathway, and its effect is self-evident [36][37][38].At present, the DET2 gene has been identified in many angiosperms and gymnosperms [23,[39][40][41][42], and few studies on woody plants have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…BRs have a wide range of physiological functions, such as plant height, plant type, flowering time, plant root growth, stem elongation, leaf extension, microtubule system development, plant morphology in dark conditions, pollen tube elongation, and seed development [33][34][35]. The main signal transduction pathways of BRs have been established, and the key gene functions of these pathways have been verified in A. thaliana; the DET2 gene is a key rate-limiting gene in brassinolide biosynthesis pathway, and its effect is self-evident [36][37][38].At present, the DET2 gene has been identified in many angiosperms and gymnosperms [23,[39][40][41][42], and few studies on woody plants have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Ethylene is a gaseous plant hormone that acts as a key regulator of many physiological processes in plants including fruit ripening; the gas has an even more marked effect on climacteric fruits (Bajguz & Piotrowska-Niczyporuk, 2023). Ethylene generates a stimulus for the expression of genes related to the ripening and senescence of fruit and vegetables and, consequently, regulates these processes in fruits such as naranjilla at the molecular, biochemical, and physiological levels (Balaguera-López, Salamanca-Gutiérrez et al, 2014).…”
Section: The Pattern Of Respiration and Ethylene Productionmentioning
confidence: 99%
“…Polyamine metabolism has been extensively investigated in higher plants [1,3]. Put is the central product of the polyamine synthesis pathway and the biosynthetic precursor of Spd and Spm [4,5]. It can be synthesized by arginine decarboxylase (ADC)-catalyzed reaction and ornithine decarboxylase (ODC)-catalyzed reaction [6].…”
Section: Introductionmentioning
confidence: 99%
“…Spd and Spm are formed by the sequential addition of aminopropyl groups provided by decarboxylated S-adenosylmethionine (dcSAM) to Put and Spd by spermidine synthase (SPDS) and spermine synthase (SPMS), respectively [7]. The dcSAM is formed by the decarboxylation reaction of S-adenosylmethionine (SAM) through S-adenosylmethionine decarboxylase (SAMDC) [5]. The oxidation of PAs is mainly carried out by diamine oxidase (DAO) and polyamine oxidase (PAO), which produces H 2 O 2 through oxidation [8].…”
Section: Introductionmentioning
confidence: 99%